Potential Risks of PM2.5 in Urban and Suburban Environments: A Dual Perspective on Chemical Constituents and Pollution Sources - Huarui Ren; Xiongping Wu; Wenchang Zhao; Jinping Cheng (Aerosol and Air Quality Research)
Abstract To investigate the chemical characteristics and source profiles of fine particulate matter (PM2.5) between suburban and urban areas, intensive observation and sample collection were conducted from November 2019 to January 2020 covering both clean and polluted days in Yulin, southwestern China. higher pollution levels were observed in urban areas during both clean and polluted days. The positive matrix factorization (PMF) receptor model and the analysis of absolute principal component scores-multiple linear regression (APCS-MLR) revealed that mixed sources and vehicle exhaust were significant contributors in both suburban and urban areas. Vehicle exhaust (36.0%), combustion sources (22.0%), and crustal dust (20.3%) were found to be the main factors affecting air quality on polluted days. The backward trajectory and the potential source contribution function (PSCF) analysis indicated that the pollution primarily originated from local sources as well as neighboring cities. According to the geo-accumulation index (Igeo), As, Cu, Pb, Se, and Zn were identified as harmful species. Moreover, non-carcinogenic risks cannot be ignored, particularly for As and V. Inhalation exposure to combustion source is identified as the primary contributor to human health risks during both clean and polluted periods. Mixed sources and industry source were the main factors causing the carcinogenic risk between suburban and urban areas.